REFLECTIONS ON THE SITUATED NATURE OF SCIENCE: CONTRIBUTIONS TO A HISTORY OF MICROBIOLOGY IN LATIN AMERICA - Augusto Matharan, Gabriel (2019)
This study aims to present an initial problematization of three dimensions, from the historiography of contemporary science, considered fundamental in order to analyse and recognize the situated character of scientific activity. Moreover, it pretends to portray how these dimensions enrich the history of microbiology in Latin America. Thus, the temporal, spatial, and gendered aspects of science are addressed. This study shows that understanding microbiology from a situated perspective in Latin America requires the acknowledgement of a multiplicity and heterogeneity of spaces, times, and gendered dimensions in all their mutual articulations.